2016
DOI: 10.1007/s11356-016-6351-8
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous abundance and redistribution patterns of rare earth elements in soils of a mining area in Inner Mongolia, China

Abstract: The Bayan Obo Mine, the largest rare earth element (REE) deposit ever found in the world, has been mined for nearly 60 years for iron and rare earth elements. To assess the influences of mining activities on geochemical behavior of REEs in soils, 27 surface soil samples and three soil profile samples were collected from different directions in the vicinity of the mine area. The total concentrations of REEs in surface soils varied from 149.75 to 18,891.81 mg kg −1 with an average value of 1906.12 mg kg, which w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 43 publications
(55 reference statements)
2
14
0
Order By: Relevance
“…Among the LREEs, Ce was the most abundant, corresponding to 47 % of the total concentration. The proportions observed for Ce and LREEs in this study were similar to those found by Wang and Liang (2016) in soils from China. In Brazil, several authors also showed Ce as the most abundant LREE, with proportions equivalent to 45 % (Silva et al, 2016), 54 % (Paye et al, 2016), and 47 % (Silva et al, 2018a).…”
Section: Natural Content Of Rees In Soilssupporting
confidence: 89%
“…Among the LREEs, Ce was the most abundant, corresponding to 47 % of the total concentration. The proportions observed for Ce and LREEs in this study were similar to those found by Wang and Liang (2016) in soils from China. In Brazil, several authors also showed Ce as the most abundant LREE, with proportions equivalent to 45 % (Silva et al, 2016), 54 % (Paye et al, 2016), and 47 % (Silva et al, 2018a).…”
Section: Natural Content Of Rees In Soilssupporting
confidence: 89%
“…The spatial variability of REEs represents the scale of change in the geology and help identify the REE hotspots and their sources (Wang and Liang, 2016). This approach helps to observe the influence of climate and parent material on REE distribution (Silva et al, 2017).…”
Section: Distribution Of Rare Earth Elements In Soilsmentioning
confidence: 99%
“…Due to disposal of these materials at the end of their useful life, the accumulation of REEs in the soil is an environmental concern (Wang and Liang, 2016). Knowledge of the natural levels of REEs in soils is the first step in monitoring potentially contaminated areas.…”
Section: Introductionmentioning
confidence: 99%
“…Rare earth elements are mainly found in halides, carbonates, oxides, phosphates, and silicates (Liang et al, 2014). The geochemistry of REEs in different parent materials and their derived soils has been previously investigated due to their importance in explaining pedogenetic (Laveuf et al, 2012;Vermeire et al, 2016), petrogenetic (Peng et al, 2014;Wang et al, 2015), and geochemical processes (Duddy, 1980;Middelburg et al, 1988;Cao et al, 2016;Wang and Liang, 2016). Rare earth elements are economically important, especially in the high-technology industry (Dutta et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The distribution of REEs in soil profiles provides information on weathering processes (Mihajlovic et al, 2014;Vermeire et al, 2016;Wang and Liang, 2016). The behavior of REEs in soil profiles depends on several factors, including the physicochemical conditions of the alteration environment and the relative stability of REE-containing primary minerals in the parent materials (Galá n et al, 2007).…”
Section: Introductionmentioning
confidence: 99%